A new occupational heat tolerance test: A feasibility study. (December 2018) - Watkins, Emily R.; Gibbons, Jemma; Dellas, Yanoula; Hayes, Mark; Watt, Peter; Richardson, Alan J.
Abstract: Heat tolerance tests identify those susceptible to heat illnesses and monitor heat adaptations. Currently, tolerance tests do not replicate the uncompensable heat strain environments experienced in some occupations. In addition, tests can take up to 2 h to complete, and cannot offer intra and inter individual comparisons, due to the use of a fixed exercise intensity. This study aimed to assess the validity and reliability of a new heat occupational tolerance test (HOTT: 40 min at 6 W kg −1 metabolic heat production, 50 °C 10% RH, in protective clothing) to the standard heat tolerance test (HTT: 2 h walk at 5 km h −1 1% gradient, 40 °C 40% RH, in shorts and t-shirt). Eighteen participants (age: 21 ± 3 yrs, body mass: 81.3 ± 5.9 kg) completed trials to assess the validity and/or reliability of the HOTT. Peak rectal temperature (Tre ) displayed strong agreement and low measurement error (0.19 °C) between HTT (38.7 ± 0.4 °C) and HOTT (38.6 ± 0.4 °C). Strong agreement was also displayed for physiological and perceptual measures between the two HOTT trials, including peak Tre (38.5 ± 0.4 °C vs. 38.5 ± 0.4 °C) and peak heart rate (182 ± 20 b min −1 vs. 182 ± 21 b min −1 ). The HOTT is the first tolerance test that assesses individuals' responses whilst wearing protective clothing in high temperatures. It can consistently identify individuals' levels of heat tolerance within a reduced time frame. In addition, it allows for participant monitoring over time and comparisons between individuals to be made. A continuum based approach is recommended when assessing individuals' responses to the HOTT. Highlights: A new occupational heat tolerance test (HOTT) set by metabolic heat production. HOTT and a standard heat tolerance test produce similar core temperature responses. The HOTT is reliable, with no differences in physiological strain between trials. The HOTT can identify heat tolerance in a shorter, uncompensable heat strain, test.